Assessment of Quality and Processing Feasibility Certificate at Frozen Tuna Loin (Thunnus sp.) Processing Unit - Aghitia Maulani; Aef Permadi; Cindy Tiara Veronica (Universitas Syiah Kuala, 2023)
Tuna is one of the economically important fish in the world fishery trade. The high demand for tuna products is a big opportunity for Indonesia as a producer in tuna exports. One of the companies engaged in handling and processing tuna on an export scale, namely PT. Tridaya Eramina Bahari which is located in Muara Baru, North Jakarta. One of the products exported is frozen tuna loin. The purpose of this study was to determine the quality and feasibility of the basic implementation of GMP and SSOP. Observation of frozen tuna loin processing is carried out directly. The organoleptic test refers to SNI 4110:2020, while sensory frozen tuna loin refers to SNI 4104:2015 which was carried out by 6 panels with 10 repetitions and 3 measurements for each observation. Microbiological and histamine tests were carried out 5 times with observations referring to SNI. Yield and productivity calculations were carried out at the loin intestine stage and cutting skinning in 3 repetitions with 3 measurements on each repetition. Processing Feasibility Certificate Assessment (SKP) refers to PermenKP No. 17 of 2019. The organoleptic test results for raw materials and sensory for frozen tuna loin products meet SNI standards. The results of microbiological and histamine testing of frozen tuna loin have complied with SNI. The results final yield is 53.29%. The results of the SKP assessment received an A rating (very good). PT. Tridaya Eramina Bahari has implemented GMP and SSOP in very good category.